Evaluating in-situ thermal transmittance measurement to analyze deviations between actual house thermal performance and modelled one by means of energy simulation software - Rezvani, Fahimeh; Zabalza Bribián, Ignacio (Revista de la Construcción. Journal of Construction, 2019)
Energy diagnosis and check of the energy performance of traditional houses are becoming urgent and essential to achieving energy saving in the residential sector. The paper presents the results of experimental studies focused on the enhancement of the methods to assess the energy efficiency in traditional houses. It is focused on U‐value as an indicator of thermal energy efficiency of traditional houses and involves in-situ measurement and the subsequent comparison with U-values calculated by a software tool. The method has been performed on thirteen walls made of stone, brick, solid mud and mixed materials. It has been concluded that in the case of masonries, the differences between the standards and in-situ measurement Uvalues varies considerably from 8% to 23.5%. Besides, these differences are within a range of 4.7% to 12.8% in the brick construction houses, due to the different thermal conductivity of brick materials.